IMPLEMENTASI MODEL PEMBELAJARAN IBL (INQUIRI BASED LEARNING) DALAM MENINGKATKAN HASIL BELAJAR KIMIA PADA TOPIK KIMIA UNSUR KELAS XII IPA 7 SMA NEGERI 7 DENPASAR TAHUN PELAJARAN 2019/2020 (LP3M Universitas PGRI Mahadewa Indonesia, 2021)
The purpose of this study was to determine whether or not the Inquiri Based Learning model was implemented in solving problems, training student activities and increasing student learning outcomes significantly. This research is a classroom action research that uses direct observation of the course of learning in class. The research was carried out at SMA Negeri 7 Denpasar. The subjects of this study were students of class XII IPA 7 at SMA Negeri 7 Denpasar in the 2019/2020 academic year which consisted of 36 students. The research focus is on work procedures in action research. The activity cycle consists of two cycles, each of which includes planning, action, observation and reflection. Learning outcomes and teacher performance in doing can be measured using tests at the end of each cycle. The results of action research show (1) The implementation of the Inquiri Based Learning learning model can increase student learning activities, (2) The implementation of the Inquiri Based Learning (IBL) learning model can improve student learning outcomes, (3) There is a significant increase in learning outcomes between pretest and the posttest value after the implementation of the Inquiri Based Learning learning model is applied to the elemental chemistry material.